Islamic militants and insurgency in northeastern Nigeria: a comparison of the ideology and methodology of Maitatsine and Boko Haram / Babayo Sule, Usman Sambo and Mohammed Kwarah Tal - Sule, Babayo; Sambo, Usman; Tal, Mohammed Kwarah (2018)
The incidence of insurgency in Northeastern Nigeria has been a phenomenon that affects socioeconomic settings of many inhabitants resulting from the devastating effects that it has in terms of destruction of lives and properties worth billions of naira from its inception. There was a perception that Boko Haram started in the early 2000s and the insurgency became formidable around 2010 but, there was the reminiscent of such insurgent attacks from Maitatsine since 1980s which is mostly neglected by researchers. The ideology and methodology of Maitatsine and Boko Haram seem similar to some extent and the problem is the root causes and how the escalation of their ideology exploded into a gory of bloodshed. This paper seeks to identify the ideology and methodology of Maitatsine and Boko Haram using comparative method. The methodology used for this work is qualitative method of data collection and analysis. The study is a conceptual theoretical paper which used thematic analytical interpretations in data gathering and research findings. The paper used secondary sources of data in the process and content analysis was used for data analysis. The paper discovered that, the ideology, method of operation and effects of Maitatsine and Boko Haram insurgencies are similar only that the magnitude and quantity of loss of lives and properties differ because of the possession of modern warfare by Boko Haram. Thus, insurgency in the region can be eliminated by identifying the root causes, prevented and deal with accordingly using military and non-military means.